Danaka Corporation : healthcare solutions portfolio management - Cooper, Robert, (SAGE Knowledge. Cases., 2017)
A major barrier for growth of large multi-business-unit firms is the inability to resource the critical initiatives to winboth in terms of dollars and people. The underpinning of the challenge involves the conflict between resourcing current cash-generating legacy businesses vs. new initiatives which may not, in the short term, produce positive financial results. Most companies do not have a formal portfolio process to deal with this fundamental issue. The Healthcare Solutions business unit of Danaka is a fictional business based on real business experiences. The principle challenge is the need for this business to free up $300 million of current, budgeted R&D projects to fund new, unfunded initiatives to meet its five-year growth objectives. Tools and processes are introduced via interactive spreadsheets that show how to make the tough portfolio decisions on a project-by-project basis.